Mitigation of Lipstick Effect and Doom Spending Through Financial Management in Supporting Sustainable Household Welfare - Pratysto, Tangguh; Aris Munandar; Moh. Najikhul Fajri; Andini Kusumawardhani; Iqbal Banyu Sunarya (FEBI UIN Sunan Kalijaga Yogyakarta, 2025)
Lipstick effect and doom spending appear simultaneously as psychological responses to economic pressures in people's spending patterns. This community service program aims to mitigate both phenomena through Islamic financial management training for students at Al-Ghozali Islamic Boarding School in Yogyakarta. Using the Asset-Based Community Development (ABCD) approach, activities include preparing Islamic financial materials, conducting interactive financial management training, and evaluating progress through pre-tests and post-tests. The program produces practical financial modules, activity reports, and scientific articles. The expected impacts include enhancing students' financial literacy, promoting healthy financial habits, and developing a sustainable financial education model grounded in Islamic values that can be replicated in other Islamic boarding schools.